Yếu tố ảnh hưởng đến ý định mua lại sản phẩm thời trang qua phát trực tiếp trên Tiktok - Phan Thị , Nhung; Nguyễn Viết, Khoa; Trần Hoàng Bảo, Lâm; Hồ Thị Thùy, Dương; Văn Thị Kim, Anh; Đỗ Thái , Nguyên; Nguyễn Hữu Nguyên, Xuân (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2021)
The study explores the factors affecting the repurchase intention (RI) of fashion products through live streaming (LS) on TikTok among young consumers in Da Nang City, based on the Stimulus-Organism-Response (SOR) framework and The Transferable Belief Model. The key contribution of this study include: (1) It is a pioneering study that explores the impact of LS platform characteristics on the formation of consumer trust, which subsequently leads to RI; (2) The study examines the role of trust transfer from sellers to product trust, which in turn influences RI. The study adopts a mixed-method approach, integrating both qualitative and quantitative techniques through partial least squares structural equation modeling (PLS-SEM) based on a survey of 300 participants. The research results confirm that LS characteristics have an impact on RI through the trust factor. These empirical research results provide additional insights for managers to formulate customer retention strategies and enhance repurchase rates effectively.